2012
DOI: 10.1055/s-0032-1309755
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pain during screening colonoscopy with an ultrathin colonoscope: a randomized controlled trial

Abstract: The new ultrathin Olympus colonoscope decreases patient pain during screening colonoscopy. This feature may improve uptake and patient satisfaction in screening colonoscopy. Further study is needed to evaluate the lower adenoma detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 12 publications
2
39
1
1
Order By: Relevance
“…Therefore, we should emphasize that only with respect to easing of UC patient discomfort and pain, was the performance of the PCF‐PQ260 type significantly better than the PCF‐Q260A conventional colonoscope type. Our findings are supported by earlier studies, which reported less patient discomfort, but without the advantage in performance for ultrathin flexible colonoscopes over a standard colonoscope . However, to our knowledge, this is the first prospective study that has evaluated an ultrathin flexible scope for colonoscopy in UC patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, we should emphasize that only with respect to easing of UC patient discomfort and pain, was the performance of the PCF‐PQ260 type significantly better than the PCF‐Q260A conventional colonoscope type. Our findings are supported by earlier studies, which reported less patient discomfort, but without the advantage in performance for ultrathin flexible colonoscopes over a standard colonoscope . However, to our knowledge, this is the first prospective study that has evaluated an ultrathin flexible scope for colonoscopy in UC patients.…”
Section: Discussionsupporting
confidence: 89%
“…Further, the new‐type scope had a flexible passive bending section at the proximal end of the conventional bending section and could easily pass through the hairpin bends of the colon. In addition, the new‐type scope had a high‐force transmission insertion tube to facilitate transmission of the force from the proximal to the distal side and could transmit greater pushing force and torque than ordinary colonoscopes …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No interventions are required to maintain a patient airway, spontaneous ventilation is adequate, and cardiovascular function is usually maintained [2]. The procedure for colonoscopy was standard and has been described elsewhere [19], with adjunct medications for anesthesia and pain control. Meperidine is an analgesic that may diminish the pain signal, however this is dose dependent [48].…”
Section: Methodsmentioning
confidence: 99%